Preparation method and application of defect-rich crystalline RuO2 porous material

The preparation of defect-rich crystalline RuO2 porous materials through impregnation heat treatment has solved the problem of easy agglomeration and low capacity of RuO2 materials, and achieved electrochemical energy storage performance with high specific capacitance. It is suitable for aqueous hydrogen ion batteries, simplifying the preparation process and reducing the production process The cost.

CN119118228AActive Publication Date: 2024-12-13BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202411241093.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The existing RuO2 materials are prone to agglomeration during the cycle, have low capacity, complex preparation steps and high cost, making it difficult to meet the needs of efficient energy storage.

Method used

Defectively rich crystalline RuO2 porous material is prepared by impregnation heat treatment. By combining high-purity tantalum foil with PS microsphere slurry and ruthenium source solution, it is dried and heat-treated to form a nanoporous RuO2 material for aqueous hydrogen storage batteries. the positive electrode material.

Benefits of technology

Reduces the process complexity of RuO2 positive electrode material, increases the specific surface area and conductivity of the material, and achieves electrochemical energy storage performance with high specific capacitance. It is suitable for a variety of water-based ion electrolytes and provides more efficient hydrogen ion storage capabilities. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118228A_ABST
    Figure CN119118228A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a defect-rich crystalline RuO2 porous material. The defect-rich crystalline RuO2 porous material is obtained by taking a high-purity tantalum foil as a current collector, coating PS microsphere slurry on the current collector to serve as an electrode plate, soaking the electrode plate in a ruthenium source solution to adsorb Ru, and performing heat treatment under a certain condition. According to the preparation method disclosed by the invention, the complexity of a RuO2 positive electrode material process can be reduced, the RuO2 positive electrode material is non-toxic, the obtained RuO2 with a nano-porous structure has a larger surface area and multiple reactive active sites, and the material can be used as a water system hydrogen storage electrode to realize storage of hydrogen ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen storage materials, and in particular relates to a defect-rich crystalline RuO2 porous material and a preparation method and application thereof. Background Art

[0002] As the environmental pollution caused by the use of fossil energy becomes more and more serious, the use of clean energy has attracted more and more attention. However, the large-scale harvest of intermittent and regional renewable energy requires efficient energy storage systems to store, distribute and utilize electricity. Therefore, people's demand for energy conversion and storage is also increasing, and it is very important to achieve energy optimization management and large-scale storage. Proton batteries have fast diffusion kinetics, are more environmentally friendly, safer, and show great competitiveness. The development of high-capacity hydrogen-ion battery positive electrode materials is of great significance. Nanoporous RuO2 material is an ideal high-capacity hydrogen-ion battery positive electrode material, but the current preparation of RuO2 material has complex operation steps, high cost and low capacity. Summary of the invention

[0003] The present invention is proposed to overcome the problems of easy agglomeration and low capacity of RuO2 materials in the prior art during the cycle process, and its purpose is to provide a defect-rich crystalline RuO2 porous material and its preparation method and application.

[0004] The present invention is achieved through the following technical solutions:

[0005] A method for preparing a defect-rich crystalline RuO2 porous material comprises the following steps:

[0006] (i) cutting a high-purity tantalum foil having a purity of ≥99.5% and a thickness of 0.05 mm into a size of 1 cm×2 cm;

[0007] (ii) ultrasonically cleaning the cut high-purity tantalum foil in ethanol and deionized water to remove surface oil and impurities, and then drying the cut high-purity tantalum foil in an oven to complete the pretreatment of the high-purity tantalum foil;

[0008] (iii) preparing PS microsphere slurry: PS microspheres (polystyrene microspheres) and LA binder are mixed and milled for 8 h at a mass ratio of 9:1 to 7:3, wherein the mass concentration of LA binder is 5%, and the solvent of LA binder is water;

[0009] (iv) The pretreated high-purity tantalum foil was used as the current collector, and the slurry was evenly coated on the foil, and then dried in an oven at 60°C to 70°C for 8h to 12h to obtain an electrode sheet; the coating amount of the PS microsphere slurry was 1mg / cm 2 ~2mg / cm 2 ;

[0010] (v) soaking the dried electrode sheet in a 0.2 mol / L ruthenium source solution for 10 min to 30 min, taking it out and letting it stand for 30 min to 60 min, rinsing it with deionized water for 15 s to 30 s, and drying it in an oven at 60° C. to 70° C. for 2 h to 3 h;

[0011] (vi) placing the electrode sheet treated in step (v) in a muffle furnace and heat treating it at 300°C to 650°C for 2h to 3h to obtain a tantalum foil-supported defect-rich crystalline RuO2 porous material.

[0012] In the above technical solution, the optimal conditions for the oven drying treatment in step (iv) are 60° C. for 8 hours.

[0013] In the above technical solution, the optimal conditions for the heat treatment in step (vi) are heat treatment at 300°C for 3 hours.

[0014] In the above technical scheme, the ruthenium source solution is a methanol solution of hydrated ruthenium chloride; the solute of the methanol solution of hydrated ruthenium chloride is hydrated ruthenium chloride, the solvent is methanol, and the solute concentration is 0.1 mol / L to 0.2 mol / L; the soaking time in step (v) is preferably 10 min; the standing time is preferably 30 min; and the rinsing time with deionized water is preferably 30 s.

[0015] A defect-rich crystalline RuO2 porous material is prepared by the above method, the rich defects are manifested in the pores, and the crystalline characteristics can be seen from XRD data.

[0016] A method for realizing hydrogen ion storage by using defect-rich crystalline RuO2 porous material, wherein the defect-rich crystalline RuO2 porous electrode material is used as a working electrode, a graphite rod or a platinum wire is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode to form a three-electrode system. + The electrolyte (0.5 mol / L sulfuric acid electrolyte) is used to assemble an aqueous proton storage half-cell to achieve hydrogen ion storage in the reaction container. Under the three-electrode system, the operating voltage window is 0V to 1V (compared to the saturated calomel electrode) and the operating temperature is 10°C to 60°C.

[0017] The beneficial effects of the present invention are:

[0018] The present invention provides a defect-rich crystalline RuO2 porous material and a preparation method and application thereof. A defect-rich crystalline RuO2 positive electrode material with a nanoporous structure is prepared by an immersion heat treatment method. The preparation method can reduce the complexity of the RuO2 positive electrode material process and is non-toxic. The obtained nanoporous structure of RuO2 has a larger surface area, which effectively increases the specific surface area and conductivity of ruthenium dioxide particles. There are many active sites for the reaction. The material can be used as an aqueous hydrogen storage electrode to achieve the storage of hydrogen ions. The present invention is mainly used to prepare nanoporous RuO2 materials as positive electrodes for use in aqueous hydrogen ion batteries, and exhibits good electrochemical energy storage properties such as high specific capacitance. The present invention has broad feasibility and is suitable for a variety of aqueous ion electrolytes. It provides conditions for subsequent expansion of preparation and commercial application, and has important application value in the preparation of hydrogen storage electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a SEM image of the defect-rich crystalline RuO2 porous material prepared in Example 1 of the present invention;

[0020] Figure 2 is a SEM image of the defect-rich crystalline RuO2 porous material prepared in Example 2 of the present invention;

[0021] Figure 3 is a SEM image of the defect-rich crystalline RuO2 porous material prepared in Example 3 of the present invention;

[0022] Figure 4 This is a SEM image (magnified 5000 times) of the defect-rich crystalline RuO2 porous material prepared in Example 3 of the present invention;

[0023] Figure 5 is the XRD pattern of the defect-rich crystalline RuO2 porous material prepared in Example 3 of the present invention;

[0024] Figure 6 This is a CV test graph of the defect-rich crystalline RuO2 porous material prepared in Example 3 of the present invention in a H2SO4 solution;

[0025] Figure 7 It is the calculated mass capacity of the defect-rich crystalline RuO2 porous material prepared in Example 3 of the present invention.

[0026] For ordinary technicians in this field, other relevant drawings can be obtained based on the above drawings without any creative work. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0028] Example 1

[0029] Preparation of defect-rich crystalline RuO2 porous materials by an impregnation heat treatment method to achieve H + The storage method is specifically carried out according to the following steps:

[0030] (i) cutting a high-purity tantalum foil having a purity of ≥99.5% and a thickness of 0.05 mm into a size of 1 cm×2 cm;

[0031] (ii) ultrasonically cleaning the high-purity tantalum foil with ethanol and deionized water respectively to remove surface oil and impurities and then drying the foil;

[0032] (iii) preparing a slurry of PS microspheres:LA binder = 9:1 and ball milling it in a ball mill for 8 h;

[0033] (iv) using the high-purity tantalum foil treated in step (ii) as a current collector, uniformly coating the slurry prepared in step (iii), and drying in an oven at 60° C. for 8 h;

[0034] (v) preparing a 0.2 mol / L hydrated ruthenium chloride-methanol solution;

[0035] (vi) soaking the electrode sheet obtained in step (iv) in the solution of step (v) for 10 min, taking it out and letting it stand for 30 min, rinsing it with deionized water for 30 s, and drying it in an oven at 60°C;

[0036] (vii) placing the obtained material in a muffle furnace and heat treating it at 300°C for 3 h to obtain a defect-rich crystalline RuO2 porous material;

[0037] (ⅷ) Prepare 0.5 mol / L (H + Sulfuric acid electrolyte with a concentration of 1.5-2.0;

[0038] (ⅸ) Assembling aqueous hydrogen storage half-cell: + In a sulfuric acid electrolyte with a concentration of 0.5 mol / L, the defect-rich crystalline RuO2 porous material obtained in step (ⅶ) is used as a working electrode, a saturated calomel electrode is used as a reference electrode, and a platinum wire is used as a counter electrode to form an electrode system at room temperature to store hydrogen ions in a reaction container.

[0039] Example 2

[0040] Based on Example 1, the difference between this example and Example 1 is that in step (iii), the ratio of PS microspheres to LA binder is 8:2.

[0041] Example 3

[0042] Based on Example 1, the only difference between this example and Example 1 is that the heat treatment temperature in step (ⅶ) is 650°C and the time is 3 hours.

[0043] Testing and Characterization:

[0044] (a) SEM test

[0045] The SEM test results show that Figure 1 , 2 3 is a scanning electron microscope photo of the materials prepared in Examples 1 to 3 at a magnification of 20,000 times, Figure 4 This is a scanning electron microscope photo of the product prepared in Example 3 at 5000 times magnification. It can be seen from the figure that after heat treatment, nanoporous RuO2 is formed on the tantalum surface. And with the improvement of the experimental method, the porous structure is more regular and uniform, with a diameter of about 1.25μm.

[0046] (b) XRD test

[0047] XRD test results are as follows Figure 5 As shown, it can be proved that the product of Example 3 after high temperature heat treatment has a crystalline structure, and its peak position is consistent with the RuO2 standard card.

[0048] (c) Electrochemical test

[0049] Figure 6 This is the CV test curve of the defect-rich crystalline RuO2 porous material prepared in Example 3 in H2SO4 solution. Figure 6 It can be seen that RuO2 has a typical rectangular CV curve of pseudocapacitance, and the mass capacity of the sample can be calculated through the area of ​​the CV curve. It is found that RuO2 has a higher capacity.

[0050] Figure 7 The mass capacity of the defect-rich crystalline RuO2 porous material prepared in Example 3 at different scan rates is measured under the following test conditions: in a 0.5 mol / L H2SO4 solution, the RuO2 nanoporous material is used as the working electrode, the platinum wire electrode is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode. Figure 7 It can be seen that even at high scan rates, RuO2 still has a high capacity and good rate performance.

[0051] In the present invention, the PS microsphere slurry provides template support; the use of methanol solution as the solvent of the ruthenium source solution can help ruthenium to better penetrate into the template and adsorb on the surface of the PS microsphere; the tantalum foil plays the role of carrying active substances in the entire synthesis process, and the tantalum still exists intact in the end. The entire synthesis process is mainly a process of using the template to adsorb active substances, and finally etching the template to retain the skeleton structure. The chemical reaction equation involved in the heat treatment process is RuCl3+O2→RuO2+Cl2.

[0052] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0053] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a defect-rich crystalline RuO2 porous material, characterized in that: (i) Preparation of electrode sheets The PS microsphere slurry is evenly coated on the surface of the pre-treated high-purity tantalum foil, and after the slurry is coated, it is dried to obtain an electrode sheet; (ii) soaking the electrode sheet prepared in step (i) in a ruthenium source solution, taking it out after soaking and letting it stand, and then washing and drying it; (iii) heat-treating the electrode sheet treated in step (ii) to obtain a tantalum foil-supported defect-rich crystalline RuO2 porous material.

2. The method for preparing defect-rich crystalline RuO2 porous material according to claim 1, characterized in that: The coating amount of PS microsphere slurry in step (i) is 1 mg / cm 2 ~2mg / cm 2 .

3. The method for preparing defect-rich crystalline RuO2 porous material according to claim 1, characterized in that: The purity of the high-purity tantalum foil is ≥99.5% and the thickness is 0.05 mm. The pretreatment method of the high-purity tantalum foil is: ultrasonically clean the high-purity tantalum foil in ethanol and deionized water respectively to remove surface oil and impurities, and then dry it in an oven.

4. The method for preparing defect-rich crystalline RuO2 porous material according to claim 1, characterized in that: The PS microsphere slurry is obtained by mixing PS microspheres and LA binder in a mass ratio of 9:1 to 7:3 and then ball milling for 8 hours; the mass concentration of the LA binder is 5%.

5. The method for preparing defect-rich crystalline RuO2 porous material according to claim 1, characterized in that: The drying temperature in step (i) is 60° C. to 70° C., and the drying time is 8 h to 12 h.

6. The method for preparing defect-rich crystalline RuO2 porous material according to claim 1, characterized in that: The ruthenium source solution is a methanol solution of hydrated ruthenium chloride; the solute of the methanol solution of hydrated ruthenium chloride is hydrated ruthenium chloride, the solvent is methanol, and the solute concentration is 0.1 mol / L to 0.2 mol / L; the soaking time in the step (ii) is 10 min to 30 min, the standing time is 30 min to 60 min, the cleaning is rinsed with deionized water for 15 s to 30 s, the drying temperature is 60°C to 70°C, and the drying time is 2h to 3h.

7. The method for preparing defect-rich crystalline RuO2 porous material according to claim 1, characterized in that: The temperature of the heat treatment in step (iii) is 300°C to 650°C, the heat treatment time is 2h to 3h, and the heat treatment atmosphere is air.

8. A defect-rich crystalline RuO2 porous material prepared by the method according to any one of claims 1 to 7, characterized in that: The material has a nanoporous structure, a pore diameter of 0.5 μm to 1.25 μm, and a pore specific surface area of ​​285 m 2 / g~300m 2 / g.

9. An application of a defect-rich crystalline RuO2 porous material prepared by the method of any one of claims 1 to 8 in hydrogen ion storage, characterized in that: The defect-rich crystalline RuO2 porous electrode material was used as the working electrode, the counter electrode, and the reference electrode to form a three-electrode system. + An aqueous hydrogen storage ion half-cell is assembled with an electrolyte to store hydrogen ions in a reaction container.

10. The use of the defect-rich crystalline RuO2 porous material in hydrogen ion storage according to claim 9, characterized in that: The counter electrode is a graphite rod or a platinum wire, and the reference electrode is a saturated calomel electrode; under the three-electrode system, the operating voltage window is 0V to 1V, and the operating temperature is 10°C to 60°C.

Citation Information

Patent Citations

  • Method for preparing RuO2 coating cathode film material of super capacitor

    CN101083171A

  • Preparation method of RuO2 material with ordered porous structure

    CN104538204A

  • Porous ruthenium dioxide and manganese dioxide combined electrode and preparation method and application thereof

    CN104868094A

  • Three-dimensional ordered porous ruthenium dioxide membrane electrode and preparation method thereof

    CN109368744A

  • Electrode with rapid ion transmission pore channels, preparation method of electrode and supercapacitor

    CN110676076A

Cited By

  • Dislocation type ruthenium dioxide catalyst as well as synthesis method and application thereof

    CN121137656A